Etiology and efficacy of anti-microbial treatment for community-acquired pneumonia in adults requiring hospital admission in Ukraine - Kaidashev, Igor; Lavrenko, Anna; Baranovskaya, Tatiana; Blazhko, Victor; Digtiar, Nataliia; Dziublyk, Oleksandr; Gerasymenko, Nataliia; Iashyna, Liudmyla; Kryvetskyi, Volodymyr; Kuryk, Lesya; Rodionova, Victoria; Stets, Roman; et al. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Empiric therapy of community-acquired pneumonia (CAP) remains the standard care and guidelines are mostly based on published data from the United States or Europe. In this study, we determined the bacterial etiology of CAP and evaluated the clinical outcomes under antimicrobial treatment of CAP in Ukraine. Methods: A total of 98 adult subjects with CAP and PORT risk II-IV were recruited for the study. The sputum diagnostic samples were obtained from all patients for causative pathogen identification. Subjects were randomly assigned in a 1:1 ratio to receive delafloxacin 300 mg (n=51) or moxifloxacin 400 mg (n=47) with blinding placebo. The switch to oral treatment was after a minimum of 6 IV doses according to clinical criteria. The total duration of antibacterial treatment was 5-10 days. In vitro susceptibility of pathogens to delafloxacin and other comparator antibiotics was determined. Results: The most frequently isolated pathogens in adults with CAP were S. pneumoniae – 19.5%, M. pneumoniae – 15.3%, H. influenzae – 13.2%, S. aureus – 10.5%, K. pneumoniae – 10.1%, and H. parainfluenzae – 6.4%. All isolates of S. pneumoniae, S. aureus, M. pneumoniae had sufficient susceptibility to appropriate antibiotics. 9.0% of H. influenzae strains were susceptible to azithromycin. 94.8 % of patients had a successful clinical response to delafloxacin at the end of treatment and 93.9 % – at test-of-cure. Conclusions: In Ukraine, the major bacterial agents that induced CAP in adults were S. pneumoniae, M. pneumoniae, H. influenzae, S. aureus, K. pneumoniae, H. parainfluenzae, E. cloacae, L. pneumophila. Delafloxacin is a promising effective antibiotic for monotherapy for CAP in adults and could be used in cases of antimicrobial-resistant strains.